Effect of storage in slurry ice on the quality and shelf life of farmed turbot (Psetta maxima) - Rodríguez, Óscar; Barros-Velázquez, Jorge; Piñeiro, Carmen; Gallardo, José Manuel; Aubourg, Santiago P. (Food Chemistry, 2006)
9 páginas, 5 figuras, 2 tablas The application of slurry ice, a binary mixture of small spherical ice crystals surrounded by seawater at subzero temperature, is a potentially new preservation method for farmed turbot (Psetta maxima), a flat fish species of increasing commercial interest. Comparative biochemical, microbiological and sensory analyses were carried on turbot specimens stored in either slurry or flake ice for up to 40 days. The results obtained in the sensory analysis correlated well with the observed chemical and microbial changes. Storage of turbot in slurry ice resulted in a slowing-down of the nucleotide degradation pathway and lipid oxidation mechanisms. A good stabilisation of the high molecular weight protein fraction of turbot muscle was also achieved as a consequence of storage in slurry ice. A slower production of both trimethylamine and total volatile bases was also observed. Likewise, low levels of total aerobes, anaerobes, coliforms, and proteolytic bacteria were attained. The application of slurry ice to farmed is advisable to achieve better quality maintenance during storage and distribution. This work was supported by a project granted by the Secretarı´a Xeral de I+D from the Xunta de Galicia (Project PGIDT01MAR40202PR). Peer reviewed